“ENHANCING PHYSICAL FITNESS IN VISUALLY IMPAIRED STUDENTS THROUGH AUDIO-GUIDED AND ADAPTIVE EXERCISES” - Qurbonova Nasiba Mirsalim qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the effectiveness of audio-guided and adaptive exercise methods in improving physical fitness among visually impaired students. The study focuses on preparatory classes where these methods are used to develop endurance, agility, balance, and coordination. The research emphasizes the importance of individualized approaches and safety measures in physical education for students with visual impairments.